Citizenship-as-knowledge: How perspectives from Bildung-centred Didaktik can contribute to European Citizenship Education beyond competence. (January 2023) - Ryen, Erik; Jøsok, Evy
How can the teaching of knowledge in schools contribute to the development of students as individual human beings, with the capacity not only for problem solving within the existing structures of society but also for developing ideas and solutions that go beyond the existing structures? The purpose of this article is to bring this question to the forefront within the context of citizenship education (CE) through a theoretical analysis of the epistemology underpinning two dominant conceptualisations of teaching CE. The analysis shows that both the model of teaching about, through and for democracy that underpins the understanding of CE in competence frameworks and the conceptualisation of CE as teaching directed towards qualification, socialisation and subjectification that is used to criticise citizenship-as-competence fall short in accounting for how knowledge can play a part in taking us beyond the existing. Turning to Bildung-centred Didaktik, which has dealt extensively with questions of knowledge in relation to the formation of the individual subject, the article explores how a renewed focus on knowledge can contribute to answering the question that Joris et al. pose in the title of their article 'Citizenship -as-competence, what else ?'